Aquaculture genome technologies - Liu, Zhanjiang. (Blackwell, 2007)
Genomics is a rapidly growing scientific field with applications ranging from improved disease resistance to increased rate of growth. Aquaculture Genome Technologies comprehensively covers the field of genomics and its applications to the aquaculture industry. This volume looks to bridge the gap between a basic understanding of genomic technology to its practical use in the aquaculture industry.